Dynamics of Evolution and Learning - Paenke, Ingo (KIT Scientific Publishing, 2008)
The book develops a unifying perspective on how learning influences evolutionary dynamics which for the first time explains seemingly contradicting results from the literature. It also reveals formerly unknown facets of the complex interplay of the two major biological adaptation mechanisms. The results apply to models from computational intelligence and evolutionary biology alike, thus contribute to the transfer of principles of biological adaptation to digital processing system.